2006
DOI: 10.1111/j.1600-0447.2006.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Two years of continued early treatment for recent‐onset schizophrenia: a randomised controlled study

Abstract: Evidence-based treatment achieves greater clinical benefits than pharmacotherapy and case management alone for recent-onset schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 44 publications
3
118
1
3
Order By: Relevance
“…These findings could reflect a strong motivation and inspiration of those family caregivers in the SPBB towards better patient care and outcomes in the community-based rehabilitation and mental healthcare service, as suggested by other family intervention studies in first-episode psychosis (Grawe et al, 2006, Petrakis et al, 2013. In line with the symptom reduction, the patients' risk and 27 frequency of re-hospitalisations in the SPBB participants were also significantly reduced (i.e., 64% and 59% reduction, respectively, at 6 months post-intervention).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings could reflect a strong motivation and inspiration of those family caregivers in the SPBB towards better patient care and outcomes in the community-based rehabilitation and mental healthcare service, as suggested by other family intervention studies in first-episode psychosis (Grawe et al, 2006, Petrakis et al, 2013. In line with the symptom reduction, the patients' risk and 27 frequency of re-hospitalisations in the SPBB participants were also significantly reduced (i.e., 64% and 59% reduction, respectively, at 6 months post-intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Self-directed, problem-solving strategies have been increasingly used or integrated into interventional studies as part of the psychosocial skills training for family caregivers or patients in an early stage of serious mental disorders, for example, schizophrenia, substance misuse and other psychotic disorders (Grawe et al, 2006, Gylnn et al, 2006, Dixon et al, 2011. Nevertheless, the effectiveness of self-help problem-solving approach to family intervention in recent-onset psychosis, or inclusion of this bibliotherapy programme, in community mental health care has not yet been studied; and thus their contributions to these families' health outcomes are uncertain (Onwumere et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…W 2010 r. Bird i wsp. opublikowali wyniki metaanalizy kilku dużych kontrolowanych badań na temat wczesnych interwencji w różnych ośrodkach na świecie -badania: COAST [93], LEO [94], OPUS [95], OTP [96], w której wykazali, że w okresie pierwszych pięciu lat trwania choroby takie wczesne i szerokie interwencje mają przewagę nad opieką standardową. Na podstawie wyników tej metaanalizy uważa się, że wczesna, kompleksowa interwencja u osób chorych na schizofrenię skutkuje istotną klinicznie redukcją ryzyka nawrotu choroby i ponownych hospitalizacji.…”
Section: Implikacje Terapeutyczneunclassified
“…The idea of early intervention programs for schizophrenic patients includes not only early detection of disorders, but also multidisciplinary, com-prehensive care for patients and their families in the form of specialized pharmacological and non-pharmacological therapy: family interventions, behavioral cognitive therapy, social skills training, and problem solving, help with getting a job and extensive psycho-educational interventions for patients and their families. In 2010, Bird et al published a meta-analysis of several large controlled studies of early intervention in different centers around the world -COAST [93], LEO [94], OPUS [95], OTP [96], in which they demonstrated that during the first five years of illness, such early and widespread interventions have the advantage over standard care. Based on the results of this meta-analysis, early intervention in schizophrenic patients is believed to result in a clinically significant reduction in the risk of relapse and re-hospitalization.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…The focus of many prior studies, however, is on interventions for groups other than adolescents, including adults with schizophrenia (Barrowclough et al, 2001;Dyck, Hendryx, Short, Voss, & McFarlane, 2002;Dyck et al, 2000;Farooq et al, 2011;Li & Arthur, 2005), first episode psychosis (Agius, Shah, Ramkisson, Murphy, & Zaman, 2007;Breitborde et al, 2011), or recent-onset schizophrenia (Grawe, Falloon, Widen, & Skogvoll, 2006;Lenior, Dingemans, Linszen, de Haan, & Schene, 2001;Lenior, Dingemans, Schene, Hart, & Linszen, 2002). Studies of siblings of adolescents with schizophrenia also have been limited (Friedrich, Lively, & Rubenstein, 2008).…”
mentioning
confidence: 99%